2019
DOI: 10.1186/s13036-019-0217-9
|View full text |Cite
|
Sign up to set email alerts
|

HMEJ-mediated efficient site-specific gene integration in chicken cells

Abstract: Background: The production of transgenic chicken cells holds great promise for several diverse areas, including developmental biology and biomedical research. To this end, site-specific gene integration has been an attractive strategy for generating transgenic chicken cell lines and has been successfully adopted for inserting desired genes and regulating specific gene expression patterns. However, optimization of this method is essential for improving the efficiency of genome modification in this species. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In another study, the HMEJ strategy was compared side-by-side with the HITIand HDR-based gene editing methods in chicken DF-1 and primordial germ cells. The results from this work showed that HMEJ was the most efficient in mediating precise gene knock-in (Xie et al, 2019). A recent publication introduced another HMEJbased approach (named GeneWeld) in which shorter homology segments of 24-48 base pairs were sufficient to drive precise reporter gene knock-in in zebrafish and mammalian cells using easily engineered donor DNA constructs in which the reporter transgene was flanked by universal gRNA target sequences (Wierson et al, 2020).…”
Section: Novel Strategies For Precise Gene Targeting In Non-dividing mentioning
confidence: 89%
“…In another study, the HMEJ strategy was compared side-by-side with the HITIand HDR-based gene editing methods in chicken DF-1 and primordial germ cells. The results from this work showed that HMEJ was the most efficient in mediating precise gene knock-in (Xie et al, 2019). A recent publication introduced another HMEJbased approach (named GeneWeld) in which shorter homology segments of 24-48 base pairs were sufficient to drive precise reporter gene knock-in in zebrafish and mammalian cells using easily engineered donor DNA constructs in which the reporter transgene was flanked by universal gRNA target sequences (Wierson et al, 2020).…”
Section: Novel Strategies For Precise Gene Targeting In Non-dividing mentioning
confidence: 89%
“…The MMEJ-based strategy was subsequently devised to an HMEJ approach by enabling more efficient targeted transgene integration using longer and more stable homology arms 27 , 37 39 . In this case, CRISPR/Cas9 is designed to cleave both the targeted genomic locus and transgene donor vector that contains long homology arms (600–900 bp each homology arm) ( Figure 3E ).…”
Section: Homology-dependent Gene Knock-in and Gene Correction Strategmentioning
confidence: 99%
“…The repair template can be in the form of circular double-stranded plasmid DNA 24 27 , single-stranded donor oligonucleotide (ssODN) 28 30 , linear double-stranded polymerase chain reaction (PCR) fragments 31 , 32 , or the homologous sequences of the intact sister chromatid 33 . Depending on the forms of repair template and CRISPR system used, homology-mediated gene insertion and replacement are carried out via specific DNA repair pathways such as homology-directed repair (HDR) 24 , 26 , 33 , synthesis-dependent strand annealing (SDSA) 28 , 34 , microhomology-mediated end joining (MMEJ) 35 , 36 , and homology-mediated end joining (HMEJ) 27 , 37 39 pathways. In homology-independent approaches, transgene knock-in and gene correction are achieved with CRISPR/Cas9 in the absence of DNA donor repair templates.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a donor template harboring microhomology arms (5-40 bp) flanking the genomic target locus, MMEJ could be used to mediate precise insertion of exogenous DNA (Figure 1 C) 48 - 51 . In addition, homology-mediated end joining (HMEJ)-based strategy with long homology arms (~800 bp) was reported to achieve precise gene integration with greater knock-in efficiency than MMEJ-based strategy (Figure 1 C) 52 - 54 .…”
Section: Introductionmentioning
confidence: 99%